2010
DOI: 10.4321/s0213-61632010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Eating attitudes and weight concern among Chinese middle-age women: A comparison between different age and BMI groups

Abstract: -Background and Objectives: Few studies have been conducted to explore eating behavior and weight concern among middle-aged women.Methods: Participants were a sample of 236 Chinese women aged 30-52. Outcome measures were various symptoms related to eating disorders, the weight concern and psychological characteristics subscales of the Eating Disorder Inventory-2 questionnaire (EDI-2). Independent variables were age, education level and BMI. ANOVA-Test and Linear Regression were performed.Results: A group of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Furthermore, Jackson and Chen [ 105 ] make a convincing case for the influence of environmental factors such as perceived pressure from mass media, interpersonal relationships, and fear of negative appearance evaluation, in the etiology of BN in adolescents. Other researchers have likewise identified the media as a perceived source of pressure relating to physical appearance, even positing that it may predict body change behaviors in both males and females [ 106 , 107 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Jackson and Chen [ 105 ] make a convincing case for the influence of environmental factors such as perceived pressure from mass media, interpersonal relationships, and fear of negative appearance evaluation, in the etiology of BN in adolescents. Other researchers have likewise identified the media as a perceived source of pressure relating to physical appearance, even positing that it may predict body change behaviors in both males and females [ 106 , 107 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of EDs in China has been advanced considerably by the publication of several larger community-based studies in the early years of 2000, which explored factors known to play a role in ED onset such as body image and eating behaviors, in male and female adolescents [ 106 , 108 , 109 ]. As a whole, these studies suggested that the incidence rates for clinical EDs were relatively low, however, they also provided indication that cases of subclinical and/or partial EDs were not uncommon, and risk factors such as body dissatisfaction and maladaptive eating behaviors, were in fact widespread.…”
Section: Introductionmentioning
confidence: 99%